Transakcje kompensacyjne w handlu Wschód—Zachód. Zarys problematyki prawnej i ekonomicznej - Sołtysiński, Stanisław (Wydział Prawa i Administracji UAM, 1983)
The increase of trade after the World War Two is usually contributed to gradual lifting up of trade barrier's and to creating a multilateral system of merchandise exchange under the auspices of GATT. Recurring practices of protectionism and return to bilateralism are presently noted and experts in the problem analyze reasons of further impediment of the developement of the world trade. A substantial part of economic and legal literature of the OECD countries is devoted today to the discussion of barter (countertrade) transactions, which are, apart to from the trade between the CMEA states, accounting for a considerable part in the East-West trade. The barter transactiones are being criticized as practices having a disruptive effect on the system of „free trade" by introducing strong elements of protectionism and bilateralism. The expansion of various forms of barter in the North- -South trade relations as well as in transactions between the developed market economy countries results in a growing discontent of the adherents of „free trade". The task of this article is an attempt to analyze the validity of economic and legal arguments advanced by critics of the barter transactions. A question whether barter practices are infringing upon obligations resulting from GATT and if they are contrary to the antitrust laws of some developed market economy countries is under the author's consideration.
Barter transactions in the East- -West trade. The outline of legal and economic problems